PENGALAMAN PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RSUD H. ANDI SULTAN DAENG RADJA BULUKUMBA - Ardhyanto Ardi; Irfanita Nurhidayah; Andi Baso Tombong (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2019)
Chronic kidney failure is progressive kidney damage that is fatal and is characterized by uremia and can lead to hemodialysis to continue living. There is a dependence on hemodialysis and the lack of research that discusses the experience of patients undergoing hemodialysis so that researchers are interested in doing this research. The purpose of this study is to explore the life experiences of chronic kidney failure patients undergoing hemodialysis at H. Andi Sultan Daeng Radja Bulukumba Hospital. Method This study uses a qualitative study (phenomenology) and a sample of 8 people with criteria for patients with chronic kidney failure undergoing hemodialysis. Data in this study were collected through in-depth interviews on selected subjects (In-depth Interviews) and analyzed using Thematic Analysis. Results Researchers found 4 themes from the results of data analysis. The themes are: (1) Early Symptoms of Disease, sub-themes: uncontrolled blood pressure, lethargy. (2) Motivation and Strengthening Undergo Therapies, sub-themes: enthusiasm from the patient himself, support of other patients undergoing hemodialysis, support from family, support from hemodialysis nurses. (3) Compliance Undergoing Treatment, sub-theme: do not delay and rule out boredom, surrender. (4) Quality of Life for Hemodialysis Patients, sub themes: feeling like a normal human being, improved diet, good weight. The quality of life of patients is better after undergoing hemodialysis therapy. Conclusions and suggestions: There are 4 themes obtained in this study. It is expected that families and nurses can provide support to patients who are undergoing hemodialysis and patients diagnosed in order to avoid fear of undergoing hemodialysis.